THE EMERGENCE OF THE JADIDISM MOVEMENT IN TURKESTAN - Akhmedov Farkhodbek Shavkatovich (American Journals Publishing, 2024)
This article is prepared on one of the most relevant topics today – “the emergence of the jadidist movement in Turkestan”, which tells about the prevalence of Enlightenment ideas in the Turkestan region and the reforms carried out by the jadids in the colonial conditions of the late 19th and early 20th centuries.